Failure modes and effects analysis (FMEA) applied to two modern radiotherapy centres - Teixeira, Nuno (2018)
FMEA is a quality improvement technique, generally applied to industry, that can provide an efficient, structured approach to assessing interconnected system failures. It is a bottom up analytical process, which identifies process hazards. According to this technique, each potential failure mode in the system is analysed to determine its effect and to classify it according to its severity. The objective is to identify reliability-critical areas in the system for which modifications to the design or maintenance procedures are required to eliminate single point failures and any catastrophic or critical consequences of such failures. Each individual component of the system is considered separately for each of its failure modes. The procedure involves the following steps: 1.Define the system and its required reliability performance. 2.Construct functional block diagrams to define and illustrate how the different sub-systems are interconnected. 3.List the components, identify their failure modes and where available their modal failure rates. 4.Complete a set of FMEA worksheets analysing the effect of each sub-assembly or component failure mode on overall system performance. Severity rankings are then assigned to each failure mode. 5.Review the worksheets to identify the reliability-critical components and make recommendations for design improvements or amendments to maintenance schedules In this work authors are presenting a FMEA study of two recent radiotherapy centres in Lisbon (Centro Oncológico Dra. Natália Chaves and Hospital CUF-Descobertas), where there are two very different radiotherapy equipments: Varian accelerator, VarisVision network and Eclipse TPS (in the first centre) and Elekta accelerator, Impac network and Xio TPS (in the second centre). This study covers a time-period of one year (all the 2004 year), and allows some very interesting conclusions related to the way the equipment behaves and how one may prevent some problems.